Competencias laborales de las secretarias ejecutivas y su influencia en la atención al personal administrativo de la Carrera de Secretariado Ejecutivo Bilingüe de la Universidad Técnica de Babahoyo en el año 2022 - Adrian Cedeño, Mayerli Rocio (2022)
The purpose of this research study is to determine what the job skills of the executive secretaries are and their influence on the attention to the administrative staff of the Bilingual Executive Secretariat career, in order to determine that the job skills in the executive secretary are knowledge, skills and attitudes that a person possesses when carrying out their work so that in this way they carry out their work, in such a way that it is efficient, it also tells us that the competencies evaluate the degree of capacity possessed by the administrative staff that works in the company where the objective The main thing is to determine what the performance of each person is. In addition, it was determined that although it is true that the administrative staff plays an important role in the company, but also over time they change the way they carry out their work. Likewise, it is worth mentioning that job skills have caused the administrative staff to be more efficient when carrying out their activities so that their job growth is much better and finally it also tells us that they are the attitudes and qualities that each person possesses. The method used in this case study was the inductive method because it allowed us to determine possible solutions to existing problems, on the other hand, it also allowed us to establish conclusions, the other method used was the deductive method, which allowed us to determine the investigation. from the general to the particular, which gave us the studied data as a result.